Supply chain performance measurement on small medium enterprise garment industry: application of supply chain operation reference - Qurtubi, Qurtubi; Yanti, Roaida; Maghfiroh, Meilinda F.N. (Jurnal Sistem dan Manajemen Industri, 2022)
In 2020, the textile industry contributed nearly 7% of Indonesia's gross domestic product. The garment industry is still dominated by small and medium enterprises (SMEs) among the textile products. Although these SMEs are considered one of the economic pillars in Indonesia, many challenges require strategical scale-up to improve their competitiveness. One of the aspects to be improved is supply chain performance, as the supply chain controls material, information, and financial flow from both supply and demand sides. This study seeks to measure and evaluate supply chain performance in the garment industry, focusing the case on small and medium-scale enterprises. The Supply Chain Operation Reference (SCOR) is used for Key Performance Index (KPI) determinants. Performance measurement starts by determining the criteria based on the performance measurement literature and expert opinion. Then, the weight of each criterion on the performance score is determined using the Analytical Hierarchy Process (AHP). Paired comparison questionnaires for the criteria weighting were distributed to experts, and the answers were analyzed. The final performance value is obtained by multiplying the weight with the normalized performance value using the Snorm-De Boer formula. This study obtained 23 indicators from five processes: plan, make, source, deliver, and return, with the final value of SCM performance classified as good. The result can evaluate the company's current condition and propose a strategy to improve its performance.